ANALISIS KINERJA PENGURUS UED-SP DALAM MENINGKATKAN EKONOMI MASYARAKAT DESA NIPAH SENDANU KECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI - ", M. Faizal; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The aim of this research was to know and to analyze UED-SP’s members performance towards problems that happened in UED-SP, for example there is no socialization that do by UED-SP’s members, the loan that do not use for business, UED-SP’s members are not looking at the society effort based on it’s productivity or not, ect. This research are focused on society economy business of saving-loan of NipahSendanu village East TebingTinggi sub-district KepulauanMeranti regency.The problem formula that use in this research were how UED-SP’s members performance of Nipah Sendanu village East Tebing Tinggi sub-district KepulauanMeranti regency and obstacle factors of UED-SP’s members Nipahsendanu village East TebingTinggi sub-district KepulauanMeranti regency. Description of phenomenon or social effect that are throught by describing dependent variable systematically and accurately. The method that have done in this research by interview, observation and library research. Kind of this research is descriptive that is researcher give explanation. The result of this research show that UED-SP’s members performance in Nipah Sendanu village East Tebing Tinggi sub-district Kepulauan Meranti regency is not yet maximal. It’s not appropriate with fundamental obligation and function of UED-SP,s members in do their obligation. The problem that happened make the UED-SP’s members performance of Nipah Sendanu village East Tebing Tinggi sub-district Kepulauan Meranti regency to be not maximal. So, cooperation all members are needed so that the result of UED-SP’s members performance to be more good than before. Keyword : Performance, members, society economy business of saving-loan